Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                

Differentiation

Download as pdf or txt
Download as pdf or txt
You are on page 1of 27

Mathematics & Elementary Statistics

PHR107

Chapter 2: Calculus

1
Differentiation

2
Recall measuring change in the case
of a linear function
For a linear equation:

The rate of change between 2 points is the slope (m), and this can
𝑦𝑦2 −𝑦𝑦1 ∆𝑦𝑦
easily be calculated using the formula slope = =
𝑥𝑥2 −𝑥𝑥1 ∆𝑥𝑥

This is slightly more complicated with curve graphs. Since a curve is


increasing and decreasing at different rates, we usually look for the
instantaneous rate of change at any particular point on the curve.

3
Gradient or Slope of Curves
• The gradient of a curve is constantly changing. You can use a tangent
to find the gradient of a curve at any point on the curve. The tangent
to a curve at a point A is the straight line that just touches the curve
at A.
• This means to find the slope of a particular point, we need the slope
of the tangent line at any point “A”.

4
5
Differentiation
• Differentiation means the rate of change of one quantity with respect to another.
• The speed is calculated as the rate of change of distance with respect to time.
This speed at each instant is not the same as the average calculated.
• Speed is the same as the slope, which is nothing but the instantaneous rate of
change of the distance over a period of time.
• The ratio of a small change in one quantity with a small change in another which
is dependent on the first quantity is called differentiation.
• One of the important concepts in calculus is mainly focused on the differentiation
of a function. The maximum or minimum value of a function, the velocity and
acceleration of moving objects, and the tangent of a curve are determined by
differentiation. If y = f(x) that is differentiable, then the differentiation is
represented as f'(x) or dy/dx.

6
Notations

7
Differentiation Rules
The differentiation rules help us to evaluate the derivatives of some particular functions,
instead of using the general method of differentiation. The process of differentiation or
obtaining the derivative of a function has the significant property of linearity.

The important rules of differentiation are:


• Constant Rule
• Power Rule
• Scalar Multiple Rule
• Sum and Difference Rule
• Product Rule
• Quotient Rule
• Chain Rule
8
Constant Rule
• The derivative of any real number, c will always be equal to zero:

9
Power Rule
• This is one of the most common rules of derivatives. If x is a variable and is raised
to a power n, then the derivative of x raised to the power is represented by:

If y = 𝑥𝑥 𝑛𝑛
𝑑𝑑𝑑𝑑 𝑑𝑑 𝑛𝑛
𝑂𝑂𝑂𝑂 (𝑥𝑥 ) = 𝑛𝑛(𝑥𝑥 𝑛𝑛−1 )
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
• This also applies to values of n which are negative for example:
1
If y = = 𝑥𝑥 −1
𝑥𝑥
𝑑𝑑 −1
(𝑥𝑥 ) = −1(𝑥𝑥 −1−1 )
𝑑𝑑𝑑𝑑
𝑑𝑑 −1 −2
−1
(𝑥𝑥 ) = −1𝑥𝑥 = 2 10
𝑑𝑑𝑑𝑑 𝑥𝑥
• The power rule can even be applied to roots of numbers:

1 1
3
If y = √𝑥𝑥 = 𝑥𝑥 2 If y = √𝑥𝑥 = 𝑥𝑥 3
𝑑𝑑 1 1−1 𝑑𝑑 3 1 1−1
�√𝑥𝑥� = �𝑥𝑥 2 � � √𝑥𝑥� = �𝑥𝑥 3 �
𝑑𝑑𝑑𝑑 2 𝑑𝑑𝑑𝑑 3
𝑑𝑑 1 −1 𝑑𝑑 3 1 −2
�√𝑥𝑥� = �𝑥𝑥 2 � � √𝑥𝑥 � = �𝑥𝑥 3 �
𝑑𝑑𝑑𝑑 2 𝑑𝑑𝑑𝑑 3
𝑑𝑑 1 𝑑𝑑 3 1
�√𝑥𝑥� = � √𝑥𝑥 � = 2
𝑑𝑑𝑑𝑑
𝑑𝑑𝑑𝑑 2√𝑥𝑥 3(𝑥𝑥 3 )

11
Scalar Multiple Rule
• In the derivation of a constant (k) multiplied with function for example,
if y = 𝑘𝑘 𝑥𝑥 2 , then only the function undergoes differentiation and not the
constant.

If y = 𝑘𝑘(𝑥𝑥 2 )
𝑑𝑑 2
𝑑𝑑 2
𝑘𝑘(𝑥𝑥 ) = 𝑘𝑘 (𝑥𝑥 )
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
𝑑𝑑
𝑘𝑘(𝑥𝑥 2 ) = 𝑘𝑘. 2𝑥𝑥
𝑑𝑑𝑑𝑑

12
Derivatives of Other Algebraic Functions
𝑑𝑑 𝑥𝑥
(𝑒𝑒 ) = 𝑒𝑒 𝑥𝑥
𝑑𝑑𝑑𝑑
𝑑𝑑 𝑥𝑥
(𝑎𝑎 ) = 𝑎𝑎 𝑥𝑥 𝑙𝑙𝑙𝑙𝑙𝑙
𝑑𝑑𝑑𝑑
𝑑𝑑 1
(𝑙𝑙𝑙𝑙𝑔𝑔𝑎𝑎 𝑥𝑥) =
𝑑𝑑𝑑𝑑 𝑥𝑥(𝑙𝑙𝑙𝑙 𝑎𝑎)
𝑑𝑑 1
(𝑙𝑙𝑙𝑙 𝑥𝑥) =
𝑑𝑑𝑑𝑑 𝑥𝑥

13
Differentiation of Trigonometric Functions

14
Sum and Difference Rule
The Sum rule says the derivative of a sum of functions is the sum of their
derivatives. The Difference rule says the derivative of a difference of functions is
the difference of their derivatives.

If y = (𝑢𝑢 ± 𝑣𝑣 )
𝑑𝑑 𝑑𝑑 𝑑𝑑
(𝑢𝑢 ± 𝑣𝑣 ) = (𝑢𝑢) ± (𝑣𝑣 )
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
The derivative of v

The derivative of u
15
Example
If y = (𝑥𝑥 2 + 𝑙𝑙𝑙𝑙𝑙𝑙)
𝑑𝑑 2 𝑑𝑑 2 𝑑𝑑
(𝑥𝑥 + 𝑙𝑙𝑙𝑙𝑙𝑙) = (𝑥𝑥 ) + (𝑙𝑙𝑙𝑙𝑙𝑙)
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
𝑑𝑑𝑑𝑑 1
= 2𝑥𝑥 +
𝑑𝑑𝑑𝑑 𝑥𝑥
If y = (sin 𝑥𝑥 − tan 𝑥𝑥)
𝑑𝑑 𝑑𝑑 𝑑𝑑
(sin 𝑥𝑥 − tan 𝑥𝑥 ) = (sin 𝑥𝑥) − (tan 𝑥𝑥 )
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
𝑑𝑑𝑑𝑑
= cos 𝑥𝑥 − sec 2 𝑥𝑥
𝑑𝑑𝑑𝑑
16
1 4
If y = 3𝑥𝑥 4
− 2+ +5
2𝑥𝑥 √𝑥𝑥
𝑑𝑑𝑑𝑑 𝑑𝑑 4
𝑑𝑑 1 𝑑𝑑 4 𝑑𝑑
= (3𝑥𝑥 ) − � 2� + � �+ (5)
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 2𝑥𝑥 𝑑𝑑𝑑𝑑 √𝑥𝑥 𝑑𝑑𝑑𝑑
𝑑𝑑𝑑𝑑 𝑑𝑑 4 1 𝑑𝑑 1 𝑑𝑑 1 𝑑𝑑 0
= 3 (𝑥𝑥 ) − � 2 � + 4 � � + 5 (𝑥𝑥 )
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 2 𝑑𝑑𝑑𝑑 𝑥𝑥 𝑑𝑑𝑑𝑑 √𝑥𝑥 𝑑𝑑𝑑𝑑
𝑑𝑑𝑑𝑑 𝑑𝑑 4 1 𝑑𝑑 −2 𝑑𝑑 1
−2
= 3 (𝑥𝑥 ) − (𝑥𝑥 ) + 4 �𝑥𝑥 � + 0
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 2 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
𝑑𝑑𝑑𝑑 1 1 −
3
= 3(4𝑥𝑥 3 ) − (−2𝑥𝑥 −3 ) + 4 �− 𝑥𝑥 2 � + 0
𝑑𝑑𝑑𝑑 2 2
𝑑𝑑𝑑𝑑 3 −3 −2
3
= 12𝑥𝑥 + 𝑥𝑥 −2𝑥𝑥
𝑑𝑑𝑑𝑑
𝑑𝑑𝑑𝑑 3
1 2
= 12𝑥𝑥 + 3 −
𝑑𝑑𝑑𝑑 𝑥𝑥 √𝑥𝑥 3 17
Practice Problems 01

18
Product Rule
According to the product rule of derivatives, if the function f(x) or y is the product
of two functions u and v, then the derivative of the function is given by:

If y = (𝑢𝑢 × 𝑣𝑣 )
𝑑𝑑 𝑑𝑑 𝑑𝑑
(𝑢𝑢 × 𝑣𝑣 ) = 𝑢𝑢 (𝑣𝑣 ) + 𝑣𝑣 (𝑢𝑢)
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑

19
Example
If y = (𝑥𝑥 2 × ln 𝑥𝑥)
If y = (sin 𝑥𝑥 × cos 𝑥𝑥 )
𝑢𝑢 = 𝑥𝑥 2 𝑎𝑎𝑎𝑎𝑎𝑎 𝑣𝑣 = 𝑙𝑙𝑛𝑛 𝑥𝑥
𝑢𝑢 = 𝑠𝑠𝑠𝑠𝑠𝑠 𝑥𝑥 𝑎𝑎𝑎𝑎𝑎𝑎 𝑣𝑣 = 𝑐𝑐𝑐𝑐𝑐𝑐 𝑥𝑥
𝑑𝑑𝑑𝑑 𝑑𝑑 𝑑𝑑 𝑑𝑑
𝑑𝑑𝑑𝑑 𝑑𝑑 𝑑𝑑 𝑑𝑑 = (𝑢𝑢 × 𝑣𝑣 ) = 𝑢𝑢 (𝑣𝑣 ) + 𝑣𝑣 (𝑢𝑢)
= (𝑢𝑢 × 𝑣𝑣 ) = 𝑢𝑢 (𝑣𝑣 ) + 𝑣𝑣 (𝑢𝑢) 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑 𝑑𝑑 2
= 𝑥𝑥 2 (ln 𝑥𝑥 ) + ln 𝑥𝑥 (𝑥𝑥 )
𝑑𝑑𝑑𝑑 𝑑𝑑 𝑑𝑑
= sin 𝑥𝑥 (cos 𝑥𝑥 ) + cos 𝑥𝑥 (sin 𝑥𝑥) 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
𝑑𝑑𝑑𝑑 2
1
𝑑𝑑𝑑𝑑 = 𝑥𝑥 � � + ln 𝑥𝑥 (2𝑥𝑥)
= sin 𝑥𝑥(− sin 𝑥𝑥) + cos 𝑥𝑥 (cos 𝑥𝑥) 𝑑𝑑𝑑𝑑 𝑥𝑥
𝑑𝑑𝑑𝑑
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑥𝑥 2
= − sin2 𝑥𝑥 + cos 2 𝑥𝑥 = � � + 2𝑥𝑥 𝑙𝑙𝑙𝑙 𝑥𝑥
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑥𝑥
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
= 𝑐𝑐𝑐𝑐𝑐𝑐 2 𝑥𝑥 − 𝑠𝑠𝑠𝑠𝑠𝑠2 𝑥𝑥 = 𝑥𝑥 + 2𝑥𝑥 𝑙𝑙𝑙𝑙 𝑥𝑥
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
20
If y = 1 − 2𝑥𝑥(sin 𝑥𝑥)
𝑢𝑢 = 1 − 2𝑥𝑥 𝑎𝑎𝑎𝑎𝑎𝑎 𝑣𝑣 = sin 𝑥𝑥
𝑑𝑑𝑑𝑑 𝑑𝑑 𝑑𝑑 𝑑𝑑
= (𝑢𝑢 × 𝑣𝑣 ) = 𝑢𝑢 (𝑣𝑣 ) + 𝑣𝑣 (𝑢𝑢)
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
𝑑𝑑𝑑𝑑 𝑑𝑑 𝑑𝑑
= 1 − 2𝑥𝑥 (sin 𝑥𝑥 ) + sin 𝑥𝑥 (1 − 2𝑥𝑥)
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
𝑑𝑑𝑑𝑑
= 1 − 2𝑥𝑥 (cos 𝑥𝑥 ) + sin 𝑥𝑥 (−2)
𝑑𝑑𝑑𝑑
𝑑𝑑𝑑𝑑
= cos 𝑥𝑥 − 2𝑥𝑥 cos 𝑥𝑥 − 2 𝑠𝑠𝑠𝑠𝑠𝑠 𝑥𝑥
𝑑𝑑𝑑𝑑

21
Practice Problems 02

22
Quotient Rule
the Quotient Rule is a method for determining the derivative (differentiation) of a
function in the form of the ratio of two differentiable functions. It is a formal rule
used in the differentiation problems in which one function is divided by the other
function.

v multiplied by the 𝑢𝑢
derivative of u If y = � �
𝑣𝑣
𝑑𝑑 𝑑𝑑
𝑑𝑑 𝑢𝑢 𝑣𝑣 (𝑢𝑢) − 𝑢𝑢 (𝑣𝑣 )
� � = 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 The value of u
𝑑𝑑𝑑𝑑 𝑣𝑣 𝑣𝑣 2 multiplied by
the derivative
of v
23
Example 1 − 2𝑥𝑥
cos 𝑥𝑥 𝐼𝐼𝑓𝑓 𝑦𝑦 = � �
𝐼𝐼𝑓𝑓 𝑦𝑦 = � � 𝑥𝑥
𝑥𝑥 𝑢𝑢 = 1 − 2𝑥𝑥 𝑎𝑎𝑎𝑎𝑎𝑎 𝑣𝑣 = 𝑥𝑥
𝑢𝑢 = cos 𝑥𝑥 𝑎𝑎𝑎𝑎𝑎𝑎 𝑣𝑣 = 𝑥𝑥 𝑑𝑑 𝑑𝑑
𝑑𝑑𝑑𝑑 𝑑𝑑 𝑢𝑢 𝑣𝑣 (𝑢𝑢) − 𝑢𝑢 (𝑣𝑣 )
𝑑𝑑 𝑑𝑑 = � �= 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
𝑑𝑑𝑑𝑑 𝑑𝑑 𝑢𝑢 𝑣𝑣 (𝑢𝑢) − 𝑢𝑢 (𝑣𝑣 ) 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑣𝑣 𝑣𝑣 2
= � �= 𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑣𝑣 𝑣𝑣 2 𝑑𝑑 𝑑𝑑
𝑑𝑑𝑑𝑑 𝑥𝑥 𝑑𝑑𝑑𝑑 (1 − 2𝑥𝑥) − (1 − 2𝑥𝑥) 𝑑𝑑𝑑𝑑 (𝑥𝑥)
𝑑𝑑 𝑑𝑑 =
𝑑𝑑𝑑𝑑 𝑥𝑥 2
𝑑𝑑𝑑𝑑 𝑥𝑥 𝑑𝑑𝑑𝑑 (𝑐𝑐𝑐𝑐𝑐𝑐 𝑥𝑥 ) − 𝑐𝑐𝑐𝑐𝑐𝑐 𝑥𝑥 𝑑𝑑𝑑𝑑 (𝑥𝑥)
= 𝑑𝑑𝑑𝑑 𝑥𝑥(−2) − (1 − 2𝑥𝑥)(1)
𝑑𝑑𝑑𝑑 𝑥𝑥 2 =
𝑑𝑑𝑑𝑑 𝑥𝑥 2
𝑑𝑑𝑑𝑑 𝑥𝑥 (−𝑠𝑠𝑠𝑠𝑠𝑠 𝑥𝑥) − 𝑐𝑐𝑐𝑐𝑐𝑐 𝑥𝑥 (1) 𝑑𝑑𝑑𝑑 −2𝑥𝑥 − 1 + 2𝑥𝑥
= =
𝑑𝑑𝑑𝑑 𝑥𝑥 2 𝑑𝑑𝑑𝑑 𝑥𝑥 2
𝑑𝑑𝑑𝑑 −𝑥𝑥 sin 𝑥𝑥 − 𝑐𝑐𝑐𝑐𝑐𝑐 𝑥𝑥 -2x and +2x
𝑑𝑑𝑑𝑑 −1
= = 2 will cancel out
𝑑𝑑𝑑𝑑 𝑥𝑥 2 𝑑𝑑𝑑𝑑 𝑥𝑥 24
Practice Problems 03

25
Chain Rule
• To differentiate y = (3x − 2)7, we could expand the brackets and then differentiate
each term separately. This would take a long time to do. There is a more efficient
method available that allows us to find the derivative without expanding.
• Let u = 3x − 2, then y = (3x − 2) 7 becomes y = u7.
• This means that y has changed from a function in terms of x to a function in terms
of u.
• We can find the derivative of the composite function y = (3x − 2) 7 using the chain
rule:
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑢𝑢
= ×
𝑑𝑑𝑑𝑑 𝑑𝑑𝑢𝑢 𝑑𝑑𝑑𝑑
26
Solution
p
If y = (3𝑥𝑥 − 2)7
Let u= 3𝑥𝑥 − 2 so y = (𝑢𝑢)7
𝑑𝑑𝑢𝑢 𝑑𝑑
= (3𝑥𝑥 − 2) = 3 With practice you will be able to do this mentally.
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑
Consider the ‘inside’ of (3x − 2)7 to be 3x − 2.
𝑑𝑑𝑦𝑦 𝑑𝑑
= (𝑢𝑢)7 = 7(𝑢𝑢)6 = 7(3𝑥𝑥 − 2)6 To differentiate (3x − 2)7:
𝑑𝑑𝑢𝑢 𝑑𝑑𝑢𝑢
Step 1: Differentiate the ‘outside’: 7(3x − 2)6
Then combine using chain rule:
Step 2: Differentiate the ‘inside’: 3
𝑑𝑑𝑑𝑑 𝑑𝑑𝑑𝑑 𝑑𝑑𝑢𝑢
= × Step 3: Multiply these two expressions: 21(3x − 2)6
𝑑𝑑𝑑𝑑 𝑑𝑑𝑢𝑢 𝑑𝑑𝑑𝑑
𝑑𝑑𝑑𝑑
= 7(3𝑥𝑥 − 2)6 × 3
𝑑𝑑𝑑𝑑
𝑑𝑑𝑑𝑑
= 21(3𝑥𝑥 − 2)6
𝑑𝑑𝑑𝑑 27

You might also like